Resource endowments and agricultural commercialization in colonial Africa: Did labour seasonality and food security drive Uganda's cotton revolution? - Michiel de Haas; Kostadis J. Papaioannou (European Historical Economics Society (EHES), 2017)
Why did some African smallholders adopt cash crops on a considerable scale, while most others were hesitant to do so? This study sets out to explore the importance of factor endowments in shaping the degrees to which cash crops were adopted in colonial tropical Africa. We conduct an in-depth case study of the 'cotton revolution' in colonial Uganda to put the factor endowments perspective to the test. Our empirical findings, based on an annual panel data analysis at the district-level from 1925 till 1960, underscore the importance of Uganda's equatorial bimodal rainfall distribution as an enabling factor for Uganda's 'cotton revolution'. We also provide evidence at a unique spatial micro-level, by capitalizing on detailed household surveys from the same period. We demonstrate that previous explanations associating variegated responses of African farmers to cash crops either to the role of colonial coercion, or to a distinction between 'forest/banana' and 'savannah/grain' zones cannot explain the widespread adoption of cotton in Uganda. We argue, instead, that the key to the cotton revolution were Uganda's two rainy seasons, which enabled farmers to grow cotton while simultaneously pursuing food security. Our study highlights the importance of food security and labour seasonality as important determinants of agricultural commercialization in colonial tropical Africa.
Keywords: N17; N57; Q17; C23; N97; 330; Agricultural Commercialization; Resource Endowments; African Economic History; Rainfall distribution; Cotton